2020
DOI: 10.1186/s12967-020-02431-8
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Accumulation of blood-circulating PD-L1-expressing M-MDSCs and monocytes/macrophages in pretreatment ovarian cancer patients is associated with soluble PD-L1

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This may be caused by the significant contribution of immune cell-derived sPD-L1 relative to tumor cell-derived sPD-L1 since immune cells also secrete PD-L1. 26 Okła et al 27 reported that PD-L1 expression was higher in immune cells infiltrating ovarian cancer tissue compared with tumor cells, and that sPD-L1 correlated with PD-L1 expression in immune cells in the blood. Keber et al 28 also found that sPD-L1 in the blood increased following resection of renal cancer, and that sPD-L1 levels correlated with PD-L1 mRNA expression in the blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be caused by the significant contribution of immune cell-derived sPD-L1 relative to tumor cell-derived sPD-L1 since immune cells also secrete PD-L1. 26 Okła et al 27 reported that PD-L1 expression was higher in immune cells infiltrating ovarian cancer tissue compared with tumor cells, and that sPD-L1 correlated with PD-L1 expression in immune cells in the blood. Keber et al 28 also found that sPD-L1 in the blood increased following resection of renal cancer, and that sPD-L1 levels correlated with PD-L1 mRNA expression in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…This may be caused by the significant contribution of immune cell–derived sPD‐L1 relative to tumor cell–derived sPD‐L1 since immune cells also secrete PD‐L1 26 . Okła et al 27 . reported that PD‐L1 expression was higher in immune cells infiltrating ovarian cancer tissue compared with tumor cells, and that sPD‐L1 correlated with PD‐L1 expression in immune cells in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint analysis. SIGLEC15, TIGIT, CD274, HAVCR2, PDCD1, CTLA4, LAG3 and PDCD1LG2 were selected as immune checkpoint-relevant transcripts (24)(25)(26)(27)(28)(29), and all the expression values of these eight genes were extracted. The aforementioned analyses and R packages were implemented in R software (version 4.0.3) using the 'ggplot2' and 'pheatmap' packages (version 4.0.3) (30)(31)(32).…”
Section: Univariate Analysis Multivariate Cox Analysis and Nomogrammentioning
confidence: 99%
“…This discrepancy was also observed in renal cell carcinoma and diffuse large B-cell lymphoma 17,25 suggesting that soluble PD-L1/2 is not a simple alternative of tissue PD-L1/2 expression. Because the main resources of soluble PD-L1 would be myeloid cells but not tumor cells., [26][27][28] tumoral PD-L1 expression and serum sPD-L1 are not necessarily correlated. Since tissue PD-L1 (CPS and TPS) indicates the immune inhibition only in the effector site, soluble PD-L1 represents the comprehensive immune inhibition in the body including lymph nodes where T cells are educated.…”
Section: No Authormentioning
confidence: 99%